Hubungan antara kecerdasan emosional dan motivasi belajar dengan hasil belajar IPA siswa SMP Negeri 1 Sungguminasa - Sitiman, Hediaty La (Jurnal Kajian Pendidikan IPA, 2021)
This research aims at: (1) discovering the students’ emotional intelligence (2) discovering the students’ learning motivation, (3) discovering the science learning outcomes , (4) examining the relationship between emotional intelligence and the science learning outcomes, (5) examining the relationship between learning motivation and the science learning outcomes, and (6) examining the relationship of both emotional intelligence and learning motivation collaboratively to the science learning outcomes at SMP Negeri 1 Sungguminasa. This research is an ex-post-facto research. The Population in this research was the students of SMP Negeri 1 Sungguminas. The sampling technique used was random sampling with the total of sample 244 students. The data collection techniques were questionnaires and documentation. The data was analyzed by employing regression test and correlation test. The results of the research reveal that: (1) the students’ emotional intelligence in general is in high category, (2) the students’ learning motivation in general is in high category, (3) the science learning outcomes in general is in high category, (4) there are positive relation signicantly between emotional intelligence and the science learning outcomes. The learning outcomes follow the improvement of emotional intelligence with coefficient level of correlation (r) is 0.492 and effective contribution R2 is 24.2%, (5) there are positive relation significantly between learning motivation and the science learning outcomes. The learning outcomes follow the improvement of learning motivation with coefficient level of correlation (r) is 0.490 and effective contribution R2 is 24%, (6) there are positive relation significantly of both emotional intelligence and learning motivation collaboratively to the science learning outcomes at SMP Negeri 1 Sungguminasa, The learning outcomes is the linear function of emotional intelligence and learning motivation, means that the science learning outcomes follow the improment of emotional intelligence and learning motivation with coefficient level of correlation (r) is 0.548 and effective contribution R2 is 30%.